How to Resolve the Trauma of Exile? Negotiating Cultural Trauma in Three Baltic Exile Plays from the 1970s North America - Nõmm , Martin (Nordic Theatre Studies, 2023)
The Estonians, Latvians, and Lithuanians who were forced to leave their respective homelands after World War II in the wake of Soviet occupation came to form exile communities across the world. These communities continued their cultural traditions and practices with the arts becoming a medium to reaffirm their identities in exile and narrate their experiences. But with a quarter of a century having passed since their migration, the 1970s became a period of re-evaluating this focus, often represented by topics of generational conflict or inability to change with the times. In North America, first generation Baltic exile playwrights Ilmar Külvet, Alfreds Straumanis, and Algirdas Landsbergis often scrutinized the condition of exile within their works. In this study, I will examine the Baltic narrative of exile as a cultural trauma and take into focus three works by these authors with representations reflecting on the changing times and crises of belonging and identity. The three plays also present a way out of these tensions and can be considered deliberate efforts by the authors to shift cultural discourse and explore other creative potentials of exile, best facilitated by negotiating between the old and the new, the traumatic past, and the ever-changing present.